A Study on Reference as Cohesive Device in Essays Written by the Fourth Semester Students of the English Study Program Universitas Riau - Nurhidayah Nurhidayah; Jismulatif Jismulatif (Universitas Riau, 2020)
This study aimed at (1) finding the types of reference as cohesive device in essays written by the fourth semester students of the English study program Universitas Riau, and (2) calculating the frequency of reference used in essays written by the fourth semester students of the English study program Universitas Riau. Documentation such as written texts was the main technique of collecting the required data. The data were analyzed by using theories from Halliday and Hassan (2013) about references as cohesive devices in the essays written by the students and by giving the percentage on the use of references. The research findings showed that all the types of reference as cohesive devices were used in the essays written by the fourth semester students with the total number of 954 devices. The most frequent reference cohesive devices used by the fourth semester students of the English study program Universitas Riau was personal reference with the percentage of 53.3% followed by demonstrative reference with the percentage of 45.8% and comparative reference with the percentage 0.9%. It could be concluded that Personal reference was the most frequently used because it may refer not only to a particular person or object, but also to any identifiable person.